A vision for the future: A proposed action plan to save the nation - Shukla, S.N. (1997)
Concerned deeply with the pervading malaise that has set in our system of governance over the past five decades, the author presents a discussion on a package of corrective measures. He suggests a 6-pronged strategy for the purpose comprising cleansing of political system (through electoral reforms), tackling corruption (through mustering political will to carry out needed changes), civil service reforms, ensuring openness and transparency, choosing right persons for constitutional positions, and population control. - Reproduced
Keywords: Public administration; Politics and government